2000
DOI: 10.1093/bja/85.4.506
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine pharmacokinetics after caudal block in 1–8 year old children

Abstract: We studied the pharmacokinetics after caudal block of ropivacaine (2 mg ml-1, 1 ml kg-1) performed in 20 children aged 1-8 yr undergoing subumbilical surgery, in this open, non-comparative, multicentre study. Venous blood samples were collected up to 12-36 h. The mean (SD) peak plasma concentration, 0.47 (0.16) mg litre-1, was achieved after 12-249 min. The free fraction was 5% and the highest individual peak plasma concentration of free ropivacaine was 0.04 mg litre-1. Clearance was 7.4 (1.9) ml min-1 kg-1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 19 publications
4
56
4
Order By: Relevance
“…19 We found that weight was a significant covariate for Vd and Cl confirming the results of Lonnqvist et al who described that age did not modify these parameters and that weight was probably the best variable to adjust dosage. 5 However, Hansen et al were able to correlate Cl with age but their population was younger than ours: these authors indeed studied very young infants and their results are probably linked to the immaturity of the hepatic metabolic pathways in these patients. They also found that the percentage of free ropivacaine was a good covariate for Cl in infants.…”
Section: Part 2: Population Analysis Using Nonmemcontrasting
confidence: 52%
See 1 more Smart Citation
“…19 We found that weight was a significant covariate for Vd and Cl confirming the results of Lonnqvist et al who described that age did not modify these parameters and that weight was probably the best variable to adjust dosage. 5 However, Hansen et al were able to correlate Cl with age but their population was younger than ours: these authors indeed studied very young infants and their results are probably linked to the immaturity of the hepatic metabolic pathways in these patients. They also found that the percentage of free ropivacaine was a good covariate for Cl in infants.…”
Section: Part 2: Population Analysis Using Nonmemcontrasting
confidence: 52%
“…1 have also been studied in various conditions demonstrating that toxic levels are rarely reached if no intravascular injection occurs. [4][5][6] However, as locoregional anesthesia is usually performed in children under general anesthesia or deep sedation, who are thus unable to report subjective signs of intravascular injection, strategies aiming at detecting early signs of accidental intravascular injection have been developed. 7 The addition of epinephrine at the concentration of at least 2.5 µg·mL -1 to the injected solution represents one of these.…”
mentioning
confidence: 99%
“…After an epidural injection of ropivacaine at 2 mg/kg, the t max is 115 and 30 min in children aged 1-2 and 5-8 years, respectively (Fig. 1b) [18]; this would probably result from the vasoconstrictive effect of ropivacaine in the epidural space [19]. Despite this prolonged t max , the C max of ropivacaine in children aged 1-2 years tends to be higher than those aged 5-8 years (0.52 vs 0.42 µg/ml), resulting from low clearance during the first 1-3 years of life.…”
Section: Pharmacokinetics Of Bupivacaine Levobupivacaine and Ropivacmentioning
confidence: 99%
“…Plasma concentration of AAG progressively increases and the fraction of unbound bupivacaine gradually decreases during the first year of life. b Plasma concentration of total ropivacaine in children aged 1-2 years (solid line) and 5-8 years (dashed line) following caudal block with 2 mg/kg ropivacaine [18]. Time to maximum concentration is 115 and 30 min; maximum concentration of total ropivacaine is 0.52 and 0.42 µg/ml in children aged 1-2 and 5−8 years, respectively <4 months than older ones after an epidural bolus 0.5 ml/ kg followed by continuous infusion at 0.25 ml/kg/h of 0.25 % bupivacaine, starting 60 min after the bolus, for 3 h and longer (0.67 ± 0.24 vs 0.27 ± 0.11 µg/ml at 3 h and 0.86 ± 0.36 vs 0.34 ± 0.12 µg/ml at 5 h) [16].…”
Section: Pharmacokinetics Of Bupivacaine Levobupivacaine and Ropivacmentioning
confidence: 99%
See 1 more Smart Citation